The Effect of Low Air Temperature on Behaviour and Milk Production in Holstein Dairy Cows - Vaculíková, Martina; Komzáková, Irena; Chládek, Gustav (Mendelova univerzita v Brně, 2017)
The aim of this study was to evaluate the influence of low air temperature on behaviour and milk production in Holstein dairy cows. The experiment was carried out at a Mendel University Farm in Žabčice, CZ, between 06-12-16 and 28-02-17. The average outdoor temperature during the above mentioned period was 2.3 oC and the average barn temperature was 1.8 oC. Other known microclimatic parametres were (in average values): relative humidity (56.9 %), refrigerating quantity (37.3 W.m-2), light intensity (326.7 lx), and air flow (0.1 - 0.4 m.sMINUS SIGN 1). The values were always measured at 10:00 am. In the experiment, 75 Holstein dairy cows were observed. These cows were housed in free-stall housing stable in which the number of boxes was higher than the number of housed cows there. The observed dairy cows were either standing (43.8 %) or lying (56.2 %). In case, they were standing, the most of them were found at trough (50.4 %), less of them were found in corridor (30.0 %), and the least of them were found in their boxes. In case, the dairy cows were lying, it was found more of them were lying on their left body side (58.7 %) and less on their right body side (43.8 %). The number of dairy cows standing in boxes had a decreasing character. Concerning the daily milk yield values, these had the same trend as the barn temperature, i.e., in 9 out of 11 cases. In this case (temperature range), the amoung of daily milk yield seems to be the best assessment factor for the infuence of temperature. It is necessary to dedicate attention to air temperature range, in which the experiment was carried out.
Keywords: air temperature; behaviour; daily milk yield; dairy cows; Holstein; microclimatic parameters; milk production